2019
DOI: 10.1002/fsn3.1331
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing synchronous extraction and antioxidant activity evaluation of polyphenols and polysaccharides from Ya'an Tibetan tea (Camellia sinensis)

Abstract: The optimal synchronous conditions to extract tea polysaccharides (TPS) and tea polyphenols (TPP) from Ya'an Tibetan tea were investigated, and the antioxidative capacity of TPS and TPP was measured, and the tea was analyzed to identify the polyphenol compounds it contained. On the basis of single-factor experiments, a Box-Behnken design and response surface methodology were applied to optimize the hot water extraction conditions. The optimal extraction technology was determined as extraction temperature of 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…It can be seen from Figure 1A that when the extraction time increased, the polysaccharide yield increased and reached a maximum at 4 h, but decreased after 4h. This is because the increase in extraction time makes it easier and faster to dissolve the polysaccharides into the solvent (Lin et al, 2017), but too long extraction time will result in the destruction of polysaccharide structure (Chen et al, 2019b;Zheng et al, 2019) and competitive dissolution of other impurities (Nuerxiati et al, 2019), leading in a decrease in yield. This phenomenon was consistent with the extraction of polysaccharides in other literatures (Wang et al, 2018b;Yang et al, 2017).…”
Section: Effect Of Extraction Time On Polysaccharide Yieldmentioning
confidence: 99%
“…It can be seen from Figure 1A that when the extraction time increased, the polysaccharide yield increased and reached a maximum at 4 h, but decreased after 4h. This is because the increase in extraction time makes it easier and faster to dissolve the polysaccharides into the solvent (Lin et al, 2017), but too long extraction time will result in the destruction of polysaccharide structure (Chen et al, 2019b;Zheng et al, 2019) and competitive dissolution of other impurities (Nuerxiati et al, 2019), leading in a decrease in yield. This phenomenon was consistent with the extraction of polysaccharides in other literatures (Wang et al, 2018b;Yang et al, 2017).…”
Section: Effect Of Extraction Time On Polysaccharide Yieldmentioning
confidence: 99%
“…sinensis and C. sinensis var. assamica (Masters) Wight [9,13]; their characteristics (i.e., appearance, organoleptic taste, chemical contents, and flavor) vary according to the fermentation level: tea can be categorized in nonfermented tea (i.e., green tea, and white tea), semifermented tea (i.e., oolong tea), and fermented tea (i.e., black tea and red tea) [5,6,9,[14][15][16][17]. The 78% of the tea worldwide production is black tea, especially consumed in Western countries, 20% consists of green tea, which is usually consumed in Asian countries, and 2% regards Oolong tea, commonly consumed in southern China [14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its chemical constituents, tea shows many beneficial properties, such as antioxidant, anti-inflammatory, antiallergic, anticarcinogenic, antidiabetic, and antimicrobial effects [6,7,9,14,15,[19][20][21]. A regular, daily consumption of green tea has been associated with many health benefits [7,22], which are mainly attributed to polyphenols, especially catechins [3,9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Fu brick tea (FBT, a brickshaped Eurotium cristatum-fermented dark tea), ECT is a daily beverage and nutritional supplement frequently consumed at the border and southern regions of China. Previous studies have shown that dark tea lowers lipid levels in the body [11] and participates in antiobesity [12], antioxidative [4], anti-inflammatory [13], and detoxification [14] processes. Further, FBT aqueous extract inhibits the mitogen-activated protein kinase (MAPK) and nuclear factor-erythroid 2-related factor-2 (Nrf2) signaling pathways in cells, thereby reducing oxidative stress levels [4].…”
Section: Introductionmentioning
confidence: 99%